The limited partnership review. Historical and comparative perspectives on the revival of a "commercial mongrel" in the United Kingdom - Henning, J. J. (Faculty of Law, University of the Free State, 2002)
The United Kingdom limited partnership can be described as the statutory equivalent of the South African partnership en commandite, which was received from French law via Roman-Dutch law. Proposed in 1838 and eventually introduced in 1907, the limited partnership has not proved as popular as its proponents would have wished for. In fact, it has been described as a "commercial mongrel" and as "dismal failure", that was sunk "almost without trace" by the private company. Nevertheless, the limited partnership presently is a useful vehicle in the United Kingdom for investors who do not wish to take an active role in the management of their funds. It offers the investor privacy, as the accounts of the partnership are not generally disclosed. Like other partnerships, it also provides the benefit of fiscal transparency. On 13 September 2000 the Law Commission of England and Wales and the Scottish Law Commission released a comprehensive joint consultation paper envisaging a thorough review of the partnership law. Consequently, the Law Commissions completed a joint consultation paper on reforms of the Limited Partnership Act 1907 which was published in November 2001. In this contribution historical and comparative perspectives are given on the proposals contained in the second joint consultation paper.

Die Engelse beperkte vennootskap kan beskou word as die statutêre eweknie van die Suid-Afrikaanse vennootskap en commandite, wat geresepieer is uit die Franse reg via die Romeins-Hollandse reg. Reeds voorgestel in 1838 en eventueel eers ingevoer in 1907, het die beperkte vennootskap nie die gewildheid verwerf as waarvoor sy voorstanders gehoop het nie. Tewens, dit is al beskryf as 'n "kommersiële baster" en as 'n "volslae mislukking", wat so die onderspit gedelf het teen die private maatskappy dat dit in die vergetelheid verdwyn het. Desnieteenstaande verskaf die beperkte vennootskap tans 'n baie bruikbare ondernemingsvorm in die Verenigde Koninkryk aan beleggers wat nie aktief wil deelneem aan die bestuur van hul fondse nie. Dit bied privaatheid aan die belegger aangesien die state van 'n beperkte vennootskap in die algemeen nie openbaar gemaak word nie. Soos ander vennootskappe, bied dit ook die voordeel van belastingdeursigtigheid. Op 13 September 2000 het die Law Commission of England and Wales en die Scottish Law Commission 'n omvattende gesamentlike konsultasiedokument vrygestel wat 'n omvattende hersiening van die vennootskapreg in die vooruitsig stel. Daaropvolgend het die twee Law Commissions 'n gesamentlike konsultasiedokument voltooi oor die hersiening van die Limited Partnership Act 1907. Dit is gepubliseer gedurende November 2001. In hierdie bydrae word beide regshistoriese en regsvergelykende perspektiewe verskaf op die voorstelle vervat in die tweede gesamentlike konsultasiedokument.